2020
DOI: 10.1038/s41598-020-58134-z
|View full text |Cite
|
Sign up to set email alerts
|

Secondary cancer risk after radiation therapy for breast cancer with different radiotherapy techniques

Abstract: the aim of this study was to estimate the radiation-related secondary cancer risks in organs during the treatment of breast cancer with different radiotherapy techniques, such as three-dimensional conformal radiotherapy (3D-CRT), intensity modulated radiotherapy (IMRT), and volumetric modulated arc therapy (VMAT). The treatment plans for 26 patients with breast cancer who received whole-breast irradiation at a dose of 50 Gy included tangential field 3D-CRT with hard-wedges (W-TF), tangential field IMRT (2F-IMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 39 publications
4
44
0
5
Order By: Relevance
“…This reduction in V5 is associated with reduction in secondary cancer [35,36] Since, ipsilateral MLD, contralateral lung V5 and breast mean doses in our study are comparable to those observed by Zhang et al, we may expect similar risk of second cancers in our patients. However, this risk may vary with distance of the organ from the sternum, patient anatomy, dose optimization, set up errors, organ motion [37] and smoking [22]. In our past series we have reported second cancers in the contralateral breast, oesophagus and lung cancers in 3.3%, 0.22% and 0.05% patients, respectively [25].…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in V5 is associated with reduction in secondary cancer [35,36] Since, ipsilateral MLD, contralateral lung V5 and breast mean doses in our study are comparable to those observed by Zhang et al, we may expect similar risk of second cancers in our patients. However, this risk may vary with distance of the organ from the sternum, patient anatomy, dose optimization, set up errors, organ motion [37] and smoking [22]. In our past series we have reported second cancers in the contralateral breast, oesophagus and lung cancers in 3.3%, 0.22% and 0.05% patients, respectively [25].…”
Section: Discussionmentioning
confidence: 99%
“…The opportunities offered by VMAT in the treatment of BC are now established, with several studies demonstrated that VMAT is the optimal photon technique in terms of target coverage, especially when IMNs are included [6,20,32]. In a study dedicated to SCR evaluation with different photon techniques in the presence of setup uncertainties, Zhang et al [36] show that the improved target coverage of VMAT comes a the price of an increased SCR. At the same time, VMAT is also associated to lower heart doses compared to tangential 3D-CRT, especially when combining with DIBH [6].…”
Section: Discussionmentioning
confidence: 99%
“…The dose and volume of irradiated tissue are regarded as one of the key factors that strongly affect secondary cancer risk (8). Cancer risk after breast radiation therapy has been well estimated (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%